Евгений Булыгин и теория юридической аргументации - Атиенза, М. (Інститут держави і права ім. В.М. Корецького НАН України, 2007)
У статті висвітлюється творчий шлях і досягнення в науці Євгена Вікторовича Булигіна, якому виповнилося
75 років. Ювіляр – відомий сучасний аргентинський філософ права, професор Університету Буенос–Айреса,
член міжнародної редакційної ради журналу «Проблеми філософії права». З позицій теорії юридичної аргументації дається всебічний аналіз філософсько-правової концепції Є. Булигіна. Переклад з англійської С. І. Максимова: Atienza, Manuel. Eugenio Bulygin and the Theory of Legal Argumentation. The paper describes the scientific carier and works of Eugenio Bulygin who has reached his 75th anniversary.
Eugenio Bulygin is a prominent contemporary Argentinean philosopher of law, Professor of University of Buenos Aires, the member of International Editorial Council of the International Journal «Philosophy of Law Issues». The comprehensive analysis of E. Bulygin’s philosophical and legal conception from the positions of the theory of legal argumentation is given in this paper. Translated from English by S. I. Maksymov.